2023
DOI: 10.1126/sciadv.adi4862
|View full text |Cite
|
Sign up to set email alerts
|

What is really known about the effects of nicotinamide riboside supplementation in humans

Abstract: Nicotinamide riboside is a precursor to the important cofactor nicotinamide adenine dinucleotide and has elicited metabolic benefits in multiple preclinical studies. In 2016, the first clinical trial of nicotinamide riboside was conducted to test the safety and efficacy of human supplementation. Many trials have since been conducted aiming to delineate benefits to metabolic health and severe diseases in humans. This review endeavors to summarize and critically assess the 25 currently published research article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Therefore, we assume that the NR acts mainly in MPP, not HSCs. A recent review assesses the currently published research articles on human NR supplementation and claims that oral NR supplementation has displayed few clinically relevant effects (Damgaard & Treebak, 2023), which is consistent with our results. Specialized BM microenvironments, termed HSC niches, maintain HSC numbers and function through cellular interactions and secreted factors that can be damaged by IR (Morrison & Scadden, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we assume that the NR acts mainly in MPP, not HSCs. A recent review assesses the currently published research articles on human NR supplementation and claims that oral NR supplementation has displayed few clinically relevant effects (Damgaard & Treebak, 2023), which is consistent with our results. Specialized BM microenvironments, termed HSC niches, maintain HSC numbers and function through cellular interactions and secreted factors that can be damaged by IR (Morrison & Scadden, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Our study has also shown that the NAD precursor supplement NR lowers NAD instead of increasing it in neurites expressing sub-heterozygous levels of NMNAT2. While NR supplementation is likely to be harmless and potentially beneficial in the majority of the population, (with no toxicity being reported so far in human studies [30]), our findings suggest that NR and possibly other NAD precursors could be problematic in a subset. As well as the known human cases with mutations in NMNAT2 , there are other conditions where the levels, activity, or transport of the protein could be compromised.…”
Section: Discussionmentioning
confidence: 67%
“…[ 18 , 28 ] However, its short stability in the circulation and NRK‐expression–limited utilization has restricted its clinical application. [ 48 , 49 ] NMN has been shown to exert beneficial effects on age‐ and diet‐induced diabetes, acute heart failure, renal injury and neurodegeneration; it also protects against cisplatin‐induced ototoxicity. [ 27 , 50 ] NMN appears to have good bioavailability, given its rapid absorption and conversion to NAD + in various organs (e.g., skeletal muscle, kidney and live), but how it is transported into cells remains unclear.…”
Section: Discussionmentioning
confidence: 99%